Whose Knowledge Is Under the Lens? A Contribution to the Debate Sparked by Clark and Walker's 2011 Research Ethics in Victimization Studies: Widening the Lens - Nourpanah, Shiva (Violence against women, 2022)
The starting point for this commentary is the fruitful exchange of ideas on the ethics of victimization research, published in this journal in 2011, sparked by Clark and Walker's article, “Research Ethics in Victimization Studies: Widening the Lens”. This article provoked a flurry of responses that, taken altogether, provide an illuminating cornerstone for the ethical debates and issues surrounding victimization research. It further inspired us to reflect upon and share our experiences on conducting victimization research at that particular intersection of academia and advocacy that we both occupy. What struck us about this exchange was the absence of any discussion about the role of anti-violence against women advocates, service providers, and organizations in victimization research.